PERSEPSI MAHASISWA TENTANG KETIDAK-JUJURAN AKADEMIK: STUDI KASUS MAHASISWA PROGRAM VOKASI UNIVERSITAS INDONESIA - Heri Yuliyanto (Program Pendidikan Vokasi Universitas Indonesia, 2015)
AbstractOften we see students gathered tasks given by the lecturers and they are copying answers betweenstudents and others. They perform this action with no load, even though the task is an individualtask. Do they know that what they are doing is an action that is contrary to the basic values ofacademic integrity. Or perhaps they are not aware that they are not a violation, since they merelyimitate or follow the habits of seniors or friends the same age. Then comes the question